The novel Dbl homology/BAR domain protein, MsgA, of Talaromyces marneffei regulates yeast morphogenesis during growth inside host cells - Harshini Weerasinghe (Nature Portfolio, 2021)
Abstract Microbial pathogens have evolved many strategies to evade recognition by the host immune system, including the use of phagocytic cells as a niche within which to proliferate. Dimorphic pathogenic fungi employ an induced morphogenetic transition, switching from multicellular hyphae to unicellular yeast that are more compatible with intracellular growth. A switch to mammalian host body temperature (37 °C) is a key trigger for the dimorphic switch. This study describes a novel gene, msgA, from the dimorphic fungal pathogen Talaromyces marneffei that controls cell morphology in response to host cues rather than temperature. The msgA gene is upregulated during murine macrophage infection, and deletion results in aberrant yeast morphology solely during growth inside macrophages. MsgA contains a Dbl homology domain, and a Bin, Amphiphysin, Rvs (BAR) domain instead of a Plekstrin homology domain typically associated with guanine nucleotide exchange factors (GEFs). The BAR domain is crucial in maintaining yeast morphology and cellular localisation during infection. The data suggests that MsgA does not act as a canonical GEF during macrophage infection and identifies a temperature independent pathway in T. marneffei that controls intracellular yeast morphogenesis.